Strengths and weaknesses of the professional improvement in Contactology of the graduate in Optometry and Optics of Pinar del Río - Muñoz Lazo, Anileidys; Mena Lorenzo, Juan Alberto; Rodríguez López, Medardo; Sixto Fuentes, Sahely (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: the professional improvement in Contactology is essential to improve the attention to patients who use contact lenses. Objective: to characterize the process of professional improvement in Contactology of the graduate in Optometry and Optics of Pinar del Río. Methods: under a dialectic approach, theoretical level methods were used, such as: historical-logical, analytical-synthetic and inductive-deductive analysis. From the empirical level: analysis of documents, observation in consultations, survey and interview. In addition, the technique of methodological triangulation of the results obtained was used. Results: the following were identified as strengths of the professional improvement process in Contactology: the interest of MINSAP in this activity, the existence of scientific-technological and human conditions for its development, the willingness of the province’s managers to cooperate, the distribution of optometrists at different levels of care and their motivation. The insufficiencies found were: the options for improvement in Contactology are isolated, limited in enrollment, and based on the needs of the secondary level of care; no improvement activities in Contactology were planned in the last five years; there are limitations in the performance of optometrists related to Contactology; and there is no strategy for improvement in Contactology at the provincial level. Conclusions: the process of professional development in Contactology is asystemic, limited, decontextualized and not comprehensive, which affects the performance of these professionals in the care of contact lens wearers at different levels of care.